2009
DOI: 10.1002/art.24498
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane BAFF from rheumatoid synoviocytes requires interleukin‐6 to induce the expression of recombination‐activating gene in B lymphocytes

Abstract: Objective. B cells that accumulate in the synovial tissue of rheumatoid arthritis (RA) patients revise their receptors due to coordinate expression of recombination-activating gene 1 (RAG-1) and RAG-2 genes. The aim of this study was to determine the mechanisms that control this re-expression.Methods. B cells from healthy control subjects were cocultured with fibroblast-like synoviocytes (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 51 publications
3
16
0
Order By: Relevance
“…First, we demonstrated that RASF constitutively produce large amount of BAFF and APRIL, expanding recent evidence of overexpression of these factors at mRNA level in RASF 17 18 36. Furthermore, we showed that TLR3 stimulation induced strong and rapid upregulation of BAFF at both mRNA and protein level while APRIL was more modestly modulated and displayed a delayed kinetic of expression, peaking 24–48 h poststimulation.…”
Section: Discussionsupporting
confidence: 74%
“…First, we demonstrated that RASF constitutively produce large amount of BAFF and APRIL, expanding recent evidence of overexpression of these factors at mRNA level in RASF 17 18 36. Furthermore, we showed that TLR3 stimulation induced strong and rapid upregulation of BAFF at both mRNA and protein level while APRIL was more modestly modulated and displayed a delayed kinetic of expression, peaking 24–48 h poststimulation.…”
Section: Discussionsupporting
confidence: 74%
“…It is interesting that in the RA joint, the accumulated B cells re-express RAG. The data from Rochas et al indicated that 2 separate signals are required for B cells to induce RAG gene expression, the first from transmembrane BAFF on RA FLS and the second from one or more cytokines, including IL-6 [90].…”
Section: Fls Interacts With B and T Cellsmentioning
confidence: 96%
“…There was no difference in BAFF mRNA of FLSs from the synovial tissue of RA patients compared with those from patients with osteoarthritis and the normal controls, but the BAFF mRNA of those cells was enhanced by IFN-γ or TNF-α [82]. In cocultures of peripheral B cells with FLSs from synovial tissue of RA patients, the expression of RAG genes-which could induce a revision of the B-cell receptor genes, resulting in autoreactivity-was induced in peripheral B cells by BAFF and IL-6 [83]. Moreover, a BAFF-dependent class switch recombination was demonstrated in the coculture of peripheral B cells with FLSs from synovial tissue of RA patients [84].…”
Section: Rheumatoid Arthritismentioning
confidence: 96%